Kehidupan narapidana di LAPAS (Lembaga Pemasyarakatan) - Egin Elga Dean Sum; Monika Veronika; Sofia Pilosusan (Indonesian Counselor Association (IKI), 2017)
LAPAS life is far from pleasant, all have rules and cannot do anything with looks. Because things that can make prisoners become frustrated and stressed. This is usually also caused by those who use them that cause them. Life experienced by prisoners is very limited and they must do anything that has been canceled by LAPAS